Association of Mortality between Diabetic and Non Diabetic Patients with Covid 19 - Memoona Hafeez, Kashif Ali Samin, Hafiz Ud Din, Sami Ullah, Muhammad Usman Sheikh, Tariq Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to determine the comparison of death rates among diabetic and non diabetic patients with coronavirus disease. Study Design: Retrospective/Observational study Place and Duration: The study was conducted at Diabetes Hospital, Peshawar and Medicine department of Avicenna Medical & Dental College and Hospital, Lahore for the duration of six months from December 2020 to May 2021. Methods: There were one hundred and fifty patients of both genders either diabetic or non diabetic with ages 20-75 years were included in this study. After receiving informed written agreement, the demographics of enrolled patients were recorded, including age, gender, BMI, and socio-economic status. All patients who had a confirmed diagnosis of COVID-19, with polymerase chain reaction testing, were included in the study. Outcomes among all patients in terms of mortality rate were recorded among all cases. We used SPSS 21.version to analyze complete data. Results: Among 150 patients, 60 (40%) cases were diabetic and 90 (60%) were non-diabetic. Mean age of the patients was 35.14±11.44 years and mean BMI 29.31±8.55 kg/m2. We found most of the cases 85 (56.7%) were males and 65 (43.3%) were females. 95 (63.3%) patients had poor socioeconomic status. Most common comorbidity was hypertension found in 68 (45.3%) cases followed by cardiovascular disease in 45 (30%) cases. Frequency of mortality in diabetic patients was significantly higher found in 35 (58.3%) cases as compared to non diabetic patients in 27 (30%) cases with p value <0.005. Conclusion: Diabetic individuals with COVID-19 showed a considerably greater death rate compared to non-diabetics. As a result, diabetes patients must be educated about the risks of infection-related hyperglycemia, the necessity of following sick-day policies, and the consequences of social isolation.